Respuestas
Respuesta dada por:
1
Listo amigo, solo reemplazas el valor de a que es en todos y listo
![\lim_{a \to \-2} \frac{ a^{4}-5}{a+1} = \frac{ 2^{4}-5}{2+1} \\ \\ = \frac{16-5}{3} = \frac{11}{3}
\lim_{a \to \-2} \frac{ a^{4}-5}{a+1} = \frac{ 2^{4}-5}{2+1} \\ \\ = \frac{16-5}{3} = \frac{11}{3}](https://tex.z-dn.net/?f=+%5Clim_%7Ba+%5Cto+%5C-2%7D++%5Cfrac%7B+a%5E%7B4%7D-5%7D%7Ba%2B1%7D+%3D+%5Cfrac%7B+2%5E%7B4%7D-5%7D%7B2%2B1%7D++%5C%5C+%5C%5C++%3D++%5Cfrac%7B16-5%7D%7B3%7D++%3D+%5Cfrac%7B11%7D%7B3%7D+%0A)
Preguntas similares
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años